Pendidikan Berbasis Lingkungan Pada Dayah Ummul Ayman 1 dan 2 - Ruslan Ruslan (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
This thesis discusses environment-based education at Dayah (traditional Islamic board school) Ummul Ayman 1 and 2, especially on the planning and implementation of environmentbased education, and the obstacles faced during its implementation. In this thesis, the study used explorative research with the inductive approach. Data were collected by observation and interview. The results of the study indicated that the planning of environmentbased education at Dayah Ummul Ayman 1 and 2 had been implemented by the teachers. This was due to firm instructions from the leaders of both schools that all teachers pay attention to the environment-based education program incorporated in the learning process. The planning of the program was developed in the learning materials of the teachers. In addition, the implementation of the program was conducted in proper stages following the relevant situation and needs as well as deeply-rooted traditions in the schools, so that the program could be wellimplemented. On the other hand, the obstacles encountered during the program implementation in both schools were not particularly significant. However, in Dayah Ummul Ayman 2, some problems occurred related to the students’ discipline as well as the teachers’. Some teachers were found smoking, making some students follow suit, although they smoked outside the school environment.